A DFT study on the mechanism of HCl and CO2 capture by CaO. Issue 3 (6th January 2022) - Ma, Xiaotong; Huang, Xingkang; Feng, Tai; Mu, Mingfei; Hu, Xiude
Abstract : HCl exhibits a preferred interaction with the O atom of CaO (100) surface, with the adsorption energy of −1.85 eV. HCl and CO2 are in competition with one another at the O site. The presence of HCl inhibits CO2 adsorption and promotes CO2 desorption. Abstract : CaO-Based materials are considered to be feasible sorbents for the removal of both HCl and CO2 . Theoretical calculations based on density functional theory (DFT) were performed to investigate the micro-mechanism of HCl/CO2 capture in a CaO-based chemical looping process. The results show that HCl preferentially interacts with surface O atoms on the CaO (100) surface, with a highest adsorption energy of −1.85 eV. The hydroxyl group, OH −, is observed during the adsorption process. At rising coverage, increased repulsion between the HCl molecules results in a lowering of the adsorption energy per HCl. The binding mechanisms of HCl and CO2 to CaO involve chemisorption and there is competing adsorption behavior between them due to positive interaction energy between coexisting HCl and CO2 . The absolute values of the absorption energy and reaction barrier for CO2 adsorption and desorption in the HCl/CaO system are much lower than those on the pristine CaO (100) surface, which indicates the inhibition of CO2 adsorption and the promotion of CO2 desorption in the presence of HCl. With HCl adsorbed, the peaks for the p orbitals of the ortho -O and para -O atoms decrease by 13% and 5% in electron density, respectively, near to the Fermi level, and the ortho peak shifts from −1.79 to −0.45 eV; these aspects are inferred to play important roles in CO2 adsorption/desorption on CaO.